2020
DOI: 10.1021/acssuschemeng.0c05872
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Dual-Emitting Ratiometric Fluorescence Sensor for Tetracyclines Detection Based on Boron Nitride Quantum Dots and Europium Ions

Abstract: On account of the excessive residues and serious detriments, it is imminent to develop an efficient method to determine tetracyclines (TCs) for protecting human health. In this work, a novel ratiometric fluorescence sensor was constructed for TCs based on a powerful boron nitride quantum dot and europium ion (BNQD-Eu 3+ ) system. The blue-emitting BNQDs were synthesized via a facile hydrothermal route using boric acid and urea as precursors. When TCs were presented in the hybrid probe of BNQDs and Eu 3+ , blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(45 citation statements)
references
References 45 publications
2
43
0
Order By: Relevance
“…4d), representing B-O and B-C groups. 33 Therefore, the B-OH bond at 193.20 eV indicated that boric acid could replace the original ligand and free boric acid appeared on the CDS surface. 29 The morphological and crystal structure of BCD was examined by using X-ray diffraction (XRD) and atomic force microscopy (AFM).…”
Section: Resultsmentioning
confidence: 99%
“…4d), representing B-O and B-C groups. 33 Therefore, the B-OH bond at 193.20 eV indicated that boric acid could replace the original ligand and free boric acid appeared on the CDS surface. 29 The morphological and crystal structure of BCD was examined by using X-ray diffraction (XRD) and atomic force microscopy (AFM).…”
Section: Resultsmentioning
confidence: 99%
“…The constant uorescence lifetime combined with the high quenching rate constant conrm the existence of SQE. [50][51][52] From the above discussion, it can be concluded that the quenching of SQDs by TC is mainly based on a combination of IFE and SQE.…”
Section: Mechanism Investigationmentioning
confidence: 95%
“…For example, Jerome et al have synthesized BNQDs by the hydrothermal method by using such a nitrogen source and boric acid dissolved in ethanol/water as the boron source [77]. The same boron and nitrogen source were used by other research groups [78] for BNQDs synthesis. Another hydrothermal method was reported by Yao et al [79] for the fabrication of BNQDs with a high QY of 32.3%.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…The ALP activity measurement was achieved in a linear range between 2 and 200 U L −1 with a low limit of detection of 0.8 U L −1 . Recently, Yang et al [78] reported an efficient method to determine tetracyclines (TCs) using ratiometric fluorescence sensors based on BNQDs and europium ion (Eu 3+ ) systems. This system worked as a probe that detected the quenching of blue fluorescence of BNQDs when introduced with TCs, while enhancing the red fluorescence of Eu 3+ .…”
Section: Chemical Sensingmentioning
confidence: 99%